Signature transcriptome analysis of stage specific atherosclerotic plaques of patients - Sonia Verma; Abhay Kumar; Rajiv Narang; Akshya K. Bisoi; Dipendra K. Mitra (BMC, 2022)
Abstract Background Inflammation plays an important role in all the stages of atherosclerotic plaque development. The current study aimed at assessing the altered expression of genes functioning in inflammation within the early stage (ES) and advanced stage (AS) atherosclerotic plaques obtained from patients undergoing coronary artery bypass grafting (CABG) surgery and identifying biomarker panel/s that may detect the status of plaque stages using peripheral blood samples. Methods A section of ES and AS plaques and normal left internal mammary arteries (LIMA) were obtained from 8 patients undergoing the CABG surgery. Total RNA isolated was analyzed for mRNA and miRNA expression profile by Affymetrix arrays. A significant number of mRNAs was found to be differentially expressed in ES and AS plaque tissues relative to LIMA. The pathway analysis of differentially expressed mRNAs in the two plaque stages was also performed using DAVID Bioinformatics Database. Results The mRNAs were found to be involved in critical inflammatory processes such as the toll-like receptor signaling pathway and cytokine-cytokine receptor interaction. Few miRNAs targeting these mRNAs were also altered in the two plaque conditions. QRT-PCR results showed a similar expression pattern of a few of the mRNAs and miRNAs in peripheral blood of the same patients relative to healthy controls. Conclusion Changes in mRNA and miRNA expression associated with various inflammatory processes occur in different atherosclerotic stage plaques as well as peripheral blood. Detection of such variations in patients' blood can be used as a possible prognostic tool to detect and/or predict the risk and stage of atherosclerosis.